The ability of Phanerochaete chrysosporium (ME446) on chemical oxygen demand remediation in submerged culture medium supplemented with malathion insecticide - Erguven, Gokhan Onder; Yildirim, Numan; Adar, Elanur (DESALINATION PUBL, 2017)
This present study aims to evaluating the efficiency of P. chrysosporium (P.c) to degrade the different concentrations of malathion (MLT) (50, 100 and 150 ppm) under agitated (130 rpm) submerged culture conditions via reduction of chemical oxygen demand (COD). We have previously screening the growth of fungus in sabouraud dextrose agar (SDA) medium for 6 days. We have also determined the laccase activity during degradation process for 15 days. According to our results the fungus has achieved 99.6, 98.8 and 98.7 % COD reduction at concentration of 50, 100 and 150 ppm respectively the end of the 15 days. The highest laccase activity (180 +/- 5.69 U/L) was measured at concentration of 50 ppm the end of the 15 days and the lowest activity (36 +/- 3.26) was determined at concentration of 150 ppm the end of the 15 days. The dried biomass of fungus was weighted at end of the 15 days and we have determined that malathion in culture medium reduced the biomass production compared the control group (SDB + P.c). Our results showed that, P. chrysosporium could be an effective bioremediation tool for treatment of malathion containing wastewater.
Keywords: P. chrysosporium; Malathion; COD reduction; Laccase activity; DEGRADATION; BIODEGRADATION; FUNGI; SOIL; BACTERIA; BIOTRANSFORMATION; LIGNINASE; OXIDATION; ORIGIN; KB2; Engineering; Water Resources